Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jtcvs.2018.07.115
|View full text |Cite
|
Sign up to set email alerts
|

Long-term transplant outcomes of donor hearts with left ventricular dysfunction

Abstract: Objective: Despite small single-center reports demonstrating acceptable outcomes using donor hearts with left ventricular dysfunction, 19% of potential donor hearts are currently unused exclusively because of left ventricular dysfunction. We investigated modern long-term survival of transplanted donor hearts with left ventricular dysfunction using a large, diverse cohort.Methods: Using the United Network for Organ Sharing database, we reviewed all adult heart transplants between January 2000 and March 2016. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…Specifically, our group has shown that higher dose norepinephrine donor support is not associated with impaired survival or higher rates of primary graft dysfunction, prolonged ventilation, or renal replacement therapy after HTX [19]. Moreover, studies have shown that recipients of donors with even markedly reduced LVEF are not at risk of impaired long-term survival, dopamine donor support is actually associated with superior survival after HTX, and recipients of donor hearts with documented single-vessel disease have similar survival when compared with recipients of donor hearts without coronary atherosclerosis [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our group has shown that higher dose norepinephrine donor support is not associated with impaired survival or higher rates of primary graft dysfunction, prolonged ventilation, or renal replacement therapy after HTX [19]. Moreover, studies have shown that recipients of donors with even markedly reduced LVEF are not at risk of impaired long-term survival, dopamine donor support is actually associated with superior survival after HTX, and recipients of donor hearts with documented single-vessel disease have similar survival when compared with recipients of donor hearts without coronary atherosclerosis [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations in the study design, the findings by Sibona and colleagues 5 are important observations that should be carefully applied to our clinical practice. These data once again demonstrate that our perceived notion of what constitutes acceptable donor criteria may no longer be valid assumptions.…”
Section: Francis D Pagani Md Phdmentioning
confidence: 90%
“…The use of extended criteria and marginal donors has expanded the donor pool for end‐stage heart failure patients with evidence of favorable outcomes in selected candidate populations. Prior studies have demonstrated comparable post‐OHT survival in recipients receiving organs with reduced ejection fraction compared to those with normal left ventricular function 4,5 . Furthermore, midterm mortality utilizing organs from older donors appears favorable 6‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…Limited donor availability for orthotopic heart transplantation (OHT) has resulted in reexamination of historical contraindications for heart transplant donors. This includes recent incorporation of the use of hepatitis C positive donors, 1,2 older donors, 3 and donors with borderline left ventricular dysfunction 4 . The use of extended criteria and marginal donors has expanded the donor pool for end‐stage heart failure patients with evidence of favorable outcomes in selected candidate populations.…”
Section: Introductionmentioning
confidence: 99%